Representation of the Message of Faith in the Lyrics of the Song” Sebelum Cahaya " by the Band Letto - Adhitama, Tias Satrio; Khoirunnisa, Khoirunnisa; Hakim, Lukman (Proceedings of International Conference on Da'wa and Communication, 2019)
Music is one of the media that is often used by preacher to preach. Poems that contain sublime can touch the hearts of listeners who are generally heterogeneous. Researchers tried to answer the question, how the lyrics of Letto's song entitled "Sebelum Cahaya'' can be represented into the messages of the creed in the point of view of da'wah science. This type of research is descriptive qualitative research. The existing data will then be analyzed using Charrles Sanders Pierce's semiotic analysis. Semiotics is the right analysis to interpret the lyrics of the song because it can be reviewed by looking at the signs of meaning contained in it. The results of this study found that the lyrics of the song contained the message of faith or belief of a servant who must hold fast to Allah SWT when going through trials or being lonely. This belief must go hand in hand with patience and prayer.